Development of a test to evaluate the psychological ability required of top athletes - Tachiya, Y.; Murakami, K.; Arai, H.; Uto, M.; Hiraki, T. (Journal of High Performance Sport, 2020)
The purpose of this study was to develop an evaluation test of the psychological abilities required by Japanese elite athletes (such as national athletes). First, 11 elite athletes and coaches were interviewed to determine what they wanted to learn about the psychological factors of elite performance and what kinds of psychological testing they were willing to attempt. Second, based on the responses, we found 32 "psychological elements" required for elite athletes and used them to develop the survey questionnaire. Third, we gathered data from 824 university student-athletes regarding the psychological elements they felt were required for elite athletes and others from the survey. Among them, further analysis was specifically conducted with 194 elite athletes who either achieved a top eight ranking in a national tournament or had previous experiences in international tournaments. As a result, we were able to identify 10 psychological factors that are important for elite athletes: self-control, concentration, imagination, confidence, consistency, self-analysis, objective approaches, goal setting, motivation, and daily life management. Also, through further analysis based on competition levels, the study found that the higher the competition level of the participants, the higher their scores of 10 psychological factors. Through these findings, we developed a test that measures the psychological abilities required for elite athletes.